Market economy and urban change : impacts in the developing world - Zetter, Roger; Hamza, Mohammed (Earthscan, 2004)
This book explores and evaluates urban sector and development policies in the context of market enablement. By articulating the linkages between this neo-liberal development paradigm and the way different actors in the urban sector enact policy responses, the book provides an understanding of both the factors driving this policy framework and the impacts of these policies on urban sector policies and programmes. In particular, the book focuses on the implications of the shift from welfare to market economies on different aspects of urban development policies and practices, particularly with regard to land, shelter and related sectoral policies for poverty alleviation. By linking policy to practice, the book seeks to inform governments, donor and implementing agencies of the impact of shifts in the development debate on urban sector strategies.